The Suborne Spotter's Guide, Birds, Flowers And Trees - Peter Holden (Usborne Publication Ltd, 2001)
Designed as a companion for enthusiasts who are keen to discover more about the natural world, this guide features colour illustrations of over 100 different species of birds, flowers and trees.